Multi-factorial profiling of athletes integrating personality, psychological skills, and psychophysiological performance indicators - Volgemute, K.; Ulme, G.; Abele, A.; Vazne, Z.; Ansons, K.; Licis, R.; Lavins, R.; Klonova, A. (Scientific Reports, 2026)
Sports performance is shaped by the interaction of various factors, including the athlete`s personality, psychological skills and psychophysiological performance. The aim of this study was to develop a multi-factorial profile of athletes, combining personality traits, psychological skills and psychophysiological performance indicators. An additional aim was to investigate the differences between team and individual sports athletes and at different levels of achievements. A total of 304 (female and male) athletes completed standardized assessments of personality traits, psychological skills and psychophysiological performance, including reaction time, stress tolerance, impulsivity, decisiveness and performance consistency. Multivariate analysis revealed significant differences between athletes taking into account the type of sport (individual vs. team), as well as the level of sport (elite, pre-elite, amateur). Cluster analysis identified four distinct athlete multi-factorial profiles. Qualitative validation by an expert panel confirmed that these profiles reflect recognizable athlete types in real training and competition contexts, providing recommendations for the implementation of practical interventions. Integrating personality, psychological skills, and psychophysiological performance indicators provides a comprehensive understanding of how athletes perform under different performance demands. These four multi-factorial profiles offer a practical framework for individual training, psychological preparation, and identification of potential risks.